European Сultural Policy of Organization of the 21st Century Socio-Cultural Sphere - Mohylevska, Nataliia (Socio-Cultural Management Journal, 2021)
Introduction. The last two decades are signed with culture meaning increase as one of the strategic priorities of the social and economic development of the EU related to the consolidation of common cultural space, management of socio-cultural activities, and development of “European citizens” identity under cross-cultural dialogue. Currently, the critical enabler of this cultural policy is special programmes. The application of the main principles of these programmes in real has been the key instrument of the European regional policy for last years. Purpose and methods. The purpose of the article is to cover the main tendencies and areas of concern of the European cultural policy based on comparative analysis of the cultural programme of the second generation. In the course of the research, the author has used the comparative, sociological, structural and functional, activity and situational-critical methods, with the help of which the features of the functioning of the above programmes were characterised. Results. Today the EU cultural policy implementation is via the prolonged “Creative Europe Programme 2021-2027” which, in comparison with other cultural programmes, is more structured and differs in an integrated approach to the organisation of the socio-cultural sphere, has incorporated all the implemented cultural and media programmes over the previous 20 years. Conclusions. In the article, there is the first analysis of the difference between the selected programmes in the context of verifying the thesis about the continuity of the programme’s principles of the EU cultural policy at the present stage, as well as the objective trend of turning cultural policy into one of the main directions of European domestic policy for the development of the socio-cultural sphere.